Supply chain and cost-benefit analyses of the community-based sea cucumber hatchery in Bargy. Bato, Sta. Cruz, Davao del Sur - Lumen, Lorenz Daniel P. (School of Management, University of the Philippines Mindanao, 2016)
Sea cucumbers provide an important contribution to the economies and livelihoods of coastal communities. High demands in the export market led to the overexploitation of these marine species, depleting stocks in the wild and threatening livelihoods. This lead to increased hatchery efforts to restore production and augment incomes of those who rely on sea cucumbers. In Brgy. Bato, a community-based sea cucumber hatchery was established. This study aimed to determine the current status of sea cucumber trade in the area; quantify the costs and benefits in putting up the community-based sea cucumber hatchery and determine its viability by conducting supply chain and cost-benefit analyses. Results of the study revealed that sea cucumbers are marketed in two forms: wet(unprocessed) and dried(processed). The study also identified and described the actors involved in the supply chain namely: gleaners, divers, fishers, middlemen, traders, exporters, and consumers. The cost-benefit analysis showed that the profit per production cycle was PhP62,355.25. From an initial cost of investment amounting to PhP 171,405.00, the ROI was at 36.38% and break-even point in terms of revenue was Php 10.977.11, having a safety margin of 87%. The results prove that the community-based sea cucumber hatchery is a viable investment however, it may only work with adequate support and proper management from the community, government institutions, non-government organizations and other private stakeholders.